Scintillation properties of high-pressure-synthesized ZnO ceramics. (November 2017) - Watanabe, Kei; Koshimizu, Masanori; Fujimoto, Yutaka; Hayashi, Yamato; Takizawa, Hirotsugu; Yanagida, Takayuki; Asai, Keisuke
Abstract: We synthesized ZnO ceramics scintillators without or with dopants using a high-pressure synthesis method. The dense ceramics were successfully obtained, and the densified structure was confirmed by SEM observation. Doping with Ga is proven to be effective for suppressing the deep level (DL) emission as well as the long decay component in the scintillation temporal profile. Based on the pulse height spectra, the light yield is estimated to be 1500 photons/5.5-MeV alpha-ray for the undoped ceramics, and the doped ceramics exhibit similar light yields. These results indicate that the high-pressure synthesis method is effective for the synthesis of dense ZnO ceramics scintillators with a fast response. Highlights: ZnO dense ceramics scintillators were developed using high-pressure synthesis. Fast response was obtained in the Ga-doped ZnO ceramics. Deep level emission was effectively suppressed by Ga doping.